TECHNIQUES OF SEMANTIZATION OF RUSSIAN VOCABULARY IN A FOREIGN LANGUAGE AUDIENCE - Popova E. I. (Academia Science Repository, 2023)
The article describes the features of conducting vocabulary and semantic work in a foreign language audience. The importance of interpreting the lexical meaning and determining the meaning of words is substantiated. The forms and methods of semantization of Russian vocabulary are considered in close connection with the nature of the lexical material, the stage of learning and the peculiarities of the perception and assimilation of Russian words by foreign students.